2021
DOI: 10.35741/issn.0258-2724.56.3.44
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy in Nigeria: Potentials and Challenges

Abstract: There is a huge renewable potential found in Nigeria which is yet to be explored. The heavy reliance on fossil fuels such as crude oil for its energy production has made it a top contributor to greenhouse gases up to 1.01 % of global emissions. Pertinent efforts have been placed on exploring renewable energy sources given the increased awareness of its sustainability. Furthermore, indicators suggest that crude oil will become a much less significant driver of the energy sector in the coming years. In the light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…[6] highlighted challenges causing low penetration of renewable energy sources in Nigeria, which is synonymous to the ones of Refs. [3,35]. The challenges include: a lack of adequate understanding and consciousness of the worth of renewable energy technologies, insufficient financial and fiscal inducements, dearth of human capital and infrastructural capacity, inadequacy of renewable energy data for plan implementation and investment decision, intermittency of renewable energy sources, high start-up investment outlays, and insufficient policy and organisational structures.…”
Section: Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] highlighted challenges causing low penetration of renewable energy sources in Nigeria, which is synonymous to the ones of Refs. [3,35]. The challenges include: a lack of adequate understanding and consciousness of the worth of renewable energy technologies, insufficient financial and fiscal inducements, dearth of human capital and infrastructural capacity, inadequacy of renewable energy data for plan implementation and investment decision, intermittency of renewable energy sources, high start-up investment outlays, and insufficient policy and organisational structures.…”
Section: Workmentioning
confidence: 99%
“…According to the authors, renewable energy includes biomass, wind, solar, hydro, geothermal, and solar energy. However, despite the enormous amount of these renewable energy sources in Nigeria and Sub-Saharan Africa, there is much reliance on non-renewable energy sources, primarily fossil fuels, with their attendant consequences [3]. These consequences include the emission of carbon dioxide, which contributes to global warming, the production of acidic rainfall that harms vegetation and stationery water bodies, and the release of toxic compounds like polycyclic aromatic hydrocarbon, and benzene, among others.…”
Section: Introductionmentioning
confidence: 99%
“…According to vulnerability analysis reported by Onah et al (2016) revealed that the northern part of Nigeria is more vulnerable to climate change compared to the southern part due to the nature of the geographical zone which is lying on the Savannah belt. This made the country one of the top contributors to GHG emissions with about 1.01% of the total global emissions (Okonkwo et al, 2021). No doubt, fossil fuel exploitation, and production in Nigeria is seen as a blessing, by putting up economic growth and drove developments of the country relatively from the revenues generated, but can also be seen on the other hand as a curse especially now that the adverse effects of oil spillage and hazardous emissions are impacting negatively on the ecosystem (Kailasam, 2006), leaving behind legacies such as gas flaring, tense climatic conditions with rising heatwaves and reclamation of land due to oil and gas extraction, were unhealthy to the environment.…”
Section: Impacts Of Climate Change In Nigeriamentioning
confidence: 99%
“…The environmental constraint is one of the main factors inhibiting the green growth in Nigerian, which was said to have affected the attainment of else-while country's vision 2020 (Okonkwo et al, 2021). In the northern part of the country the desert encroachment is mainly caused by the combination of rising heat and less rain, loss of the wetlands, and fast reduction in the amount of surface water, flora, and fauna resources on land (Abdulkadir et al, 2018), whereas other coastal areas are battling with rising sea levels and flooding (Coster & Adeoti, 2015).…”
Section: Impacts On the Ecologymentioning
confidence: 99%
See 1 more Smart Citation